The Effect of Pseudomonas aeruginosa Bacteria and Yeast of Kluyveromyces marxianus in Growth of Rhizoctonia solani Fungi in Laboratory and Different Temperature and Campestral Deep of Soil - Ebtesam Thamer Jeaz (Al-Qadisiyah Journal For Agriculture Sciences, 2016)
This study has been conducted to evaluate the efficacy of the yeast K.marxianus and P.aeruginosa bacteria separately against R.solani caused root rot , P.aeruginosa show high efficacy as a biological agent against R.solani on PDA with 100% inhibition at 108 cell/ ml. In addition , K.marxianus in concentration 10 8 cell/ ml inhibited R.solani growth at 88 % as compared with 0.0% in control , P.aeruginosa suspension at 10 8 cell/ml and its filtrate inhibited spores germination and rate of germ tubes length to 0.0 of R.solany completely . K.marxianus suspension at 10 8 cell/ml inhibited spores germination with 2.1% , rate of germ tubes length reach to 8 micrometer while K.marxianus filtrate 10 8 cell/ ml inhibition germ germination with 2.2% , rate of germ tubes lenghth reached to 9 micrometer while control (R.solani ) germ germination reach to 97% , germ tubes length with 25 micrometer . R.solani Produces three enzymes helped of pathogenicity (pectinase, cellulose and protease ) without lipase .These fungus not growth in temperatures 10 c to 27 day , at the temperatures ( 35, 40, 45)c to 14 day and in temperature 50 c to 25 day but R. solani fungus growth in temperature 12 c to 20 day while optimum growth of fungus is in 20 c to 18 day , 25 c to 17 day and 30 c in 16 day . R.solani founded in depth (1,7,10,13) cm but if is not founded in depth 16 cm